(untitled) (Bangladesh Medical Journal, 2025)
One of the most important tools in urology for a range of treatments is DJS. By keeping the ureter open, these stents reduce edema and allow for possible injury. DJS after URS with ICPL is debatable. However, a number of short- and long-term challenges have been linked to the DJS; for example, hematuria, infection, discomfort, and stent syndrome are all short-term complications. Total 98 individuals with ureteral calculi who visited the Department of Urology during the study period comprised the study population. The Department of Urology at BSMMU, Bangladesh, conducted this prospective comparative study over the period of a year, from November 2022 to November 2023. The purpose of this study was to assess the benefits and drawbacks of post-operative DJS following URS surgery with ICPL. Patients were enrolled in this study after obtaining their written consent. Later, they were split up into two groups. After URS+ICPL, patients in Group A received DJS, but those in Group B did not. Interviews were conducted with each patient to learn more about their clinical and demographic characteristics. Each patient’s detailed medical history was documented, including the size and location of the stones, stone free rate, pain and complications as well as the duration of the procedure and hospital stay. DJS following URS+ICPL was evaluated based on stone free rate, ambulatory, pain and complications. Data were analyzed by statistical package for social sciences (SPSS) version 22.0. Mean age of the patients was 39.88 ± 11.44 years in DJS group and 38.10 ± 10.24 years in no DJS group. Males (62%; group-A 32%, group-B 29%) were predominant than females (38%; group-A 17%, group-B 20%) in both the two groups but there was no significant difference between the two groups. In both groups, the percentages of DM (12.2% vs 14.3%) and HTN (22.4% vs 18.4%) were nearly equal. There was no significant difference in BMI, Systolic BP and Diastolic BP between the two groups. In both the DJS and no DJS groups, the left-sided stones outnumbered the right-sided ones. In both the DJS and no DJS groups, the highest percentage of stones were found in the lower calix (40.8% vs. 42.9%), followed by the middle calix (36.7% vs. 38.8%) and the upper calix (22.4% vs. 18.4%). The stone sizes in the DJ and non-DJ stent groups were 22.67 ± 4.16 mm and 20.08 ± 2.57 mm, respectively. Compared to the no DJS group (87.8%), the stone clearance was significantly lower in the DJS group (71.4%). Compared to the no DJS group (59.2%), the ambulatory rate was significantly lower in the DJS group (38.8%). The DJS group spent more times (1.32 ± 0.89 days) in the hospital, compared to less times (1.10 ± 0.30 days) in the non-DJS group (p>0.05). The group with a DJS experienced considerably more complications overall (42.9%) than the non-DJS group (22.4%). Hematuria was less frequent (8.2%) in the non-DJS group and more frequent (18.4) in the DJS group (p>0.05). Both fever (14.3%) and pain (14.3%) experienced in non-DJS groups is equal; where 24.5% fever and 42.9% pain experienced respectively, in the DJS and non-DJS groups (p<0.05). Steinstrasse was 10.2% in DJS group and 6.1% in no non-DJS group (p>0.05). Following URS and ICPL, DJ stenting significantly reduces stone clearance and ambulation rates compared to no stenting, and is associated with increased complications. Omitting DJ stenting after ureteroscopy appears safe. Bangladesh Med J. 2024 Sept; 53(3): 1-6